Location and angulation of curvatures of mesiobucal canals of mandibular molars debrided by three endodontic techniques Posição e angulação de curvaturas radiculares em canais mesiobucais de molares inferiores preparados por três técnicas endodônticas - Isa Geralda Teixeira Constante; Harry Davidowicz; Fernando Branco Barletta; Abilio Albuquerque Maranhão de Moura (Sociedade Brasileira de Pesquisa Odontológica, 2007)
The aim of this study was to assess the correlation between the degree of angulation and the position of root curvatures and their influence on the comparative results between the performances of the Progressive, Staged and Serial Preparation Techniques. The mesiobucal canals of 70 extracted mandibular molars were filled with a radiological contrast of 100% Barium sulphate and radiographed with a direct digital radiographic system, in an apparatus that guarantees that the samples remain in the same spatial position at all times. The images were then analyzed in the Coreldraw 10 program (MicroSafe, RJ, Brasil) in accordance with two criteria: the methods of Berbert, Nishiyama¹ (1994) and Schneider11 (1971) to determine the position and the angle of the root curvatures, respectively. Initially, the possibility of correlation between these two variables was studied. The teeth were then selected according to angulation (greater than 25 degrees) and position of root curvatures (cervical, median and apical) in order to perform the endodontic techniques. After preparation, the samples were radiographed again and the images were superimposed in order to compare the pre- and post-operative areas. The difference between them showed the percentage of widening for each technique. The results showed that there was no correlation between the angulations and the root curvature positions, and that the different positions did not interfere in the performance of the techniques. The Progressive Preparation technique produced the highest widening values for all the groups, irrespective of the root curvature position. O objetivo deste trabalho foi verificar a correlação entre o grau de angulação e a posição das curvaturas radiculares, e a sua influência nos resultados comparativos entre os desempenhos das técnicas do Preparo Progressivo, Escalonada e Seriada. Os canais mésio-vestibulares de 70 dentes molares inferiores extraídos foram preenchidos com um contraste radiológico de sulfato de Bário a 100% e radiografados em um sistema de radiografia digital direta, em um aparato que garantia que as amostras ficassem sempre na mesma posição espacial. As imagens foram, então, analisadas no programa Coreldraw 10 (MicroSafe, RJ, Brasil) segundo dois critérios: os métodos de Berbert, Nishiyama¹ (1994) e de Schneider11 (1971) para determinação da posição e do ângulo das curvaturas radiculares, respectivamente. Estudou-se inicialmente a possibilidade de correlação entre essas duas variáveis. Os dentes foram, então, selecionados segundo a angulação (superior a 25 graus) e posição das curvaturas radiculares (cervical, mediana e apical) para a realização das técnicas endodônticas. Após os preparos, as amostras foram novamente radiografadas e as imagens sobrepostas para a comparação das áreas pré e pós-operatórias. A diferença entre elas mostrou a porcentagem de alargamento para cada técnica. Os resultados mostraram não existir correlação entre as angulações e as posições das curvaturas radiculares, e que as diferentes posições não interferem no desempenho das técnicas. A técnica do Preparo Progressivo mostrou maiores valores de alargamento para todos os grupos, independentemente da posição da curvatura radicular.